Characterization and clinical evaluation of a novel 2D detector array for conventional and flattening filter free (FFF) IMRT pre-treatment verification - Sekar, Yuvaraj; Thölking, Johannes; Eckl, Miriam; Kalichava, Irakli; Sihono, Dwi Seno Kuncoro; Wenz, Frederik; Wertz, Hansjörg (Zeitschrift für medizinische Physik, 2018)
Background and purpose: The novel MatriXXFFF (IBA Dosimetry, Germany) detector is a new 2D ionization chamber detector array designed for patient specific IMRT-plan verification including flattening-filter-free (FFF) beams. This study provides a detailed analysis of the characterization and clinical evaluation of the new detector array. Material and methods: The verification of the MatriXXFFF was subdivided into (i) physical dosimetric tests including dose linearity, dose rate dependency and output factor measurements and (ii) patient specific IMRT pre-treatment plan verifications. The MatriXXFFF measurements were compared to the calculated dose distribution of a commissioned treatment planning system by gamma index and dose difference evaluations for 18 IMRT-sequences. All IMRT-sequences were measured with original gantry angles and with collapsing all beams to 0° gantry angle to exclude the influence of the detector's angle dependency. Results: The MatriXXFFF was found to be linear and dose rate independent for all investigated modalities (deviations ≤0.6%). Furthermore, the output measurements of the MatriXXFFF were in very good agreement to reference measurements (deviations ≤1.8%). For the clinical evaluation an average pixel passing rate for γ(3%,3mm) of (98.5±1.5)% was achieved when applying a gantry angle correction. Also, with collapsing all beams to 0° gantry angle an excellent agreement to the calculated dose distribution was observed (γ(3%,3mm)=(99.1±1.1)%). Conclusions: The MatriXXFFF fulfills all physical requirements in terms of dosimetric accuracy. Furthermore, the evaluation of the IMRT-plan measurements showed that the detector particularly together with the gantry angle correction is a reliable device for IMRT-plan verification including FFF.